Modified coating building ceramic composite material and preparation method thereof

CN122916612APending Publication Date: 2026-10-16ENPING XINJINCHENG CERAMICS CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611265059.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该方案说明表面强化层能够改善建筑陶瓷的整体力学性能,但其主要解决普通陶瓷的预应力强化问题,并未针对高比例废陶瓷原料因表面活性低、界面相容性不足而导致的强度下降进行设计,也不能直接解决为保证废料陶瓷强度而需要增加高铝质增强原料的问题

Benefits of technology

[0041] 1. This invention uses waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass as the main recycled raw materials for building ceramics, which can improve the resource utilization of construction waste in ceramic products and reduce the consumption of natural ceramic mineral raw materials. At the same time, by using modified coatings to undertake part of the strengthening effect, the use of high-alumina reinforcing raw materials such as calcined bauxite in the body can be reduced, which is conducive to reducing raw material costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the technical field of ceramic composite materials, in particular to a modified coating building ceramic composite material and a preparation method thereof. Waste ceramic, waste sintered clay brick and waste building glass are used as building waste raw materials to prepare a ceramic body, and an inner transition layer and an outer strengthening layer are formed on the surface of the ceramic body in sequence; the inner transition layer contains boron-silicon-aluminum composite modified waste ceramic micro powder obtained by sequentially surface modifying an aluminum-containing component and a boron-silicon component; and then the body is co-fired with the double-layer modified coating. The application can improve the sintering combination between the waste ceramic particles and the coating and the ceramic matrix, reduce the interface defects, improve the mechanical properties of the building ceramic composite material while reducing the use amount of the high-aluminum reinforcing raw material, and realize the resource utilization of the building waste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic composite materials technology, specifically to a modified coated building ceramic composite material and its preparation method. Background Technology

[0002] The production of architectural ceramics and the demolition and renovation of buildings generate a large amount of inorganic solid waste, including waste ceramics, waste bricks, and waste glass. This waste contains a high proportion of SiO2, Al2O3, and alkali metal and alkaline earth metal oxides, providing a resource base for reuse in ceramic material preparation. However, the waste ceramics have already undergone high-temperature firing, resulting in the near loss of plasticity of their clay minerals and reduced surface reactivity. Re-adding them to ceramic bodies can easily lead to insufficient bonding between particles and between waste ceramic particles and the newly formed sintered phase. Existing technologies typically compensate for the decline in mechanical properties caused by the addition of high proportions of solid waste by adding plasticizers, sintering aids, or high-alumina reinforcing materials. However, this increases raw material costs and fails to fundamentally improve the interfacial bonding of waste ceramic particles.

[0003] Chinese invention patent application CN115650698A discloses a method for recycling waste porcelain and ceramic bricks. It uses waste porcelain powder (80-88% by weight) as the main raw material for the ceramic brick body, and improves the plasticity, powder packing, and sintering density of the waste porcelain powder by adding plasticizers, lubricants, and sintering aids, thereby enhancing the overall performance of the ceramic bricks. This method can achieve a high proportion of waste porcelain recycling, but it mainly improves molding and sintering performance by adding plasticizers and sintering aids inside the ceramic brick body. It lacks targeted surface control measures for the interfacial bonding defects between the already fired waste porcelain particles and the newly formed ceramic phase.

[0004] Chinese invention patent application CN118125800A discloses a waste ceramic powder and its application in ceramic bricks. Addressing the issues of low activity and poor bonding with other raw materials after high-temperature firing, it employs plasma treatment to pulverize the waste ceramic powder and further coats its surface with a SiO2 film to improve its dispersibility and sintering properties. Simultaneously, it combines hybrid fibers and a specific surface glaze to enhance the performance of the ceramic bricks. This solution demonstrates that surface treatment of waste ceramic particles is beneficial for improving their reusability. However, the plasma activation and hybrid fiber system require high-level production equipment and process control. Furthermore, it uses a single SiO2 surface coating and does not involve sequentially treating the waste ceramic powder with aluminum-containing and borosilicate components and then using it as an inner transition layer between the green body and the outer reinforcing layer.

[0005] Chinese invention patent application CN113264783A discloses a prestressed ceramic and its preparation method. By setting a prestressed layer with a coefficient of thermal expansion lower than that of the ceramic body on the surface, the ceramic can utilize surface prestress to offset part of the external tensile stress, thereby improving the strength and toughness of the ceramic. The prestressed layer mainly uses raw materials such as calcite, kaolin, quartz, spodumene, zinc oxide, barium carbonate, and frit. This scheme demonstrates that the surface strengthening layer can improve the overall mechanical properties of building ceramics. However, it primarily addresses the prestressing strengthening problem of ordinary ceramics and does not address the strength reduction caused by high proportions of waste ceramic raw materials due to low surface activity and insufficient interfacial compatibility. Furthermore, it does not directly solve the problem of needing to add high-alumina reinforcing materials to ensure the strength of waste ceramics.

[0006] Therefore, although existing technologies have proposed technical solutions such as high-proportion waste ceramic recycling, waste ceramic surface activation, and ceramic surface prestressing strengthening, it is still necessary to provide a building ceramic composite material and its preparation method that can take into account high-proportion resource utilization of construction waste, interface strengthening of waste ceramic particles, and reduction of the use of high-alumina reinforcing raw materials. Summary of the Invention

[0007] To address the shortcomings of the existing technology, this invention provides a modified coated building ceramic composite material and its preparation method.

[0008] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a modified coated building ceramic composite material includes the following steps:

[0010] (1) Mix construction waste raw materials, including waste ceramics and waste building glass, with ceramic matrix, and obtain building ceramic blanks by ball milling and granulation. Then, press the building ceramic blanks into shapes to obtain ceramic green bodies.

[0011] (2) An inner transition layer and an outer reinforcing layer are sequentially formed on the surface of the ceramic green body; wherein, the raw materials of the inner transition layer include waste ceramic powder, borosilicate aluminum composite modified waste ceramic powder, waste glass powder, wollastonite and aluminosilicate raw materials, and the raw materials of the outer reinforcing layer include wollastonite, quartz powder and aluminosilicate raw materials.

[0012] The boron-silicon-aluminum composite modified waste ceramic powder is obtained by sequentially modifying waste ceramic powder with an aluminum-containing component and a boron-silicon component including silica sol and boric acid.

[0013] (3) The ceramic green body with the inner transition layer and the outer reinforcing layer is sintered to make the ceramic green body, the inner transition layer and the outer reinforcing layer co-fired and combined to obtain the modified coating building ceramic composite material.

[0014] Preferably, the aluminosilicate raw material is an inorganic mineral raw material that can provide SiO2 and Al2O3 components during ceramic firing, and is preferably selected from at least one of kaolin, calcined kaolin and mullite powder.

[0015] Preferably, the preparation method of the building ceramic blank is as follows: Based on a total solid raw material weight of 100 parts, weigh 37-41 parts of waste ceramic wall and floor tiles, 18-22 parts of waste sintered clay bricks, 10-14 parts of waste building glass, 14-18 parts of kaolin, 6-10 parts of potassium-sodium feldspar, 1-5 parts of calcined bauxite, and 1-3 parts of bentonite, with each of the above solid raw materials selected within the range mentioned above and a total weight of 100 parts; mix the above raw materials and add them to a ball mill according to a mass ratio of solid raw materials, grinding balls, and water of 1:(1.5-2.5):(0.6-1.0), ball mill for 1-2 hours, and pass through a 150-250 mesh sieve; dry the resulting slurry at 80-100℃, pulverize it, add 4.5-6.5% water relative to the dry powder mass for granulation, pass through a 16-24 mesh sieve, and seal and age for 8-16 hours to obtain the building ceramic blank.

[0016] The inner transition layer is obtained by coating the surface of the ceramic green body with an inner transition layer slurry. The solid raw materials of the inner transition layer slurry are prepared as follows, with a total solid raw material weight of 100 parts: 12-22 parts waste ceramic powder, 4-12 parts borosilicate aluminum composite modified waste ceramic powder, 25-35 parts waste glass powder, 24-32 parts wollastonite, 12-18 parts calcined kaolin and 1-3 parts zinc oxide are mixed, 40-55 parts water, 0.20-0.40 parts sodium polyacrylate and 0.20-0.50 parts sodium carboxymethyl cellulose are added, and the mixture is ball-milled for 1-3 hours and passed through a 400-600 mesh sieve to obtain the inner transition layer slurry.

[0017] Preferably, the outer reinforcing layer is obtained by coating the surface of the ceramic green body with an outer reinforcing layer slurry. The solid raw materials of the outer reinforcing layer are prepared as follows, based on a total of 100 parts by weight: 52-64 parts of wollastonite, 16-24 parts of quartz powder, 7-12 parts of calcined kaolin, 7-13 parts of waste glass powder and 2-4 parts of zinc oxide are mixed, 40-55 parts of water, 0.20-0.40 parts of sodium polyacrylate and 0.20-0.50 parts of sodium carboxymethyl cellulose are added, and the mixture is ball-milled for 1-3 hours and passed through a 400-600 mesh sieve to obtain the outer reinforcing layer slurry.

[0018] Preferably, in step (1), the construction waste raw materials include waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass, and the ceramic base material includes kaolin, potassium sodium feldspar, calcined bauxite and bentonite; based on a total of 100 parts by weight of solid raw materials for building ceramic blanks, the calcined bauxite is 1-5 parts by weight.

[0019] Preferably, in the inner transition layer, the borosilicate-aluminum composite modified waste ceramic powder accounts for 4-12% of the total mass of the solid raw materials in the inner transition layer, and the total amount of waste ceramic powder and borosilicate-aluminum composite modified waste ceramic powder accounts for 20-30% of the total mass of the solid raw materials in the inner transition layer.

[0020] Preferably, the solid raw material of the inner transition layer further includes zinc oxide, and the aluminosilicate raw material includes calcined kaolin; the solid raw material of the outer reinforcing layer further includes waste glass powder and zinc oxide.

[0021] When using a high proportion of waste ceramic wall and floor tiles, the waste ceramics have already undergone one high-temperature firing, reducing the plasticity of the original clay minerals and lowering the surface reactivity of the particles. When they are sintered again with newly added ceramic raw materials such as kaolin and feldspar, pores and weak bonding areas easily form between the waste ceramic particles and the surrounding liquid phase and newly formed sintered phase. Traditional methods of increasing the overall strength by adding high-alumina reinforcing materials such as calcined bauxite can strengthen the body skeleton, but they cannot specifically solve the problem of insufficient interfacial bonding of waste ceramic particles and increase the amount of raw materials used and production costs.

[0022] Preferably, the preparation method of the borosilicate-aluminum composite modified waste ceramic micro powder includes:

[0023] Waste ceramic powder was dispersed in water, aluminum salt solution was added and the system was adjusted to alkalinity so that the aluminum-containing precursor component was loaded on the surface of the waste ceramic powder.

[0024] Subsequently, a borosilicate-modified component, including silica sol and boric acid, was added for composite surface modification. After drying and pulverizing, the borosilicate-aluminum composite modified waste ceramic powder was obtained.

[0025] This invention first pretreats the surface of waste ceramic powder with an aluminum-containing component, then uses silica sol and boric acid for composite modification, so that the aluminum, silicon, and boron components are preferentially distributed on the surface of the waste ceramic particles. During co-firing, the silicon-aluminum component helps improve the compositional continuity between the surface of the waste ceramic particles and the surrounding silicon-aluminum sintered phase, while the boron component helps promote the formation of a local liquid phase and wetting of the waste ceramic particles, thereby promoting the formation of a denser bonding area between particles and between the waste ceramic particles and the surrounding sintered phase, reducing interfacial porosity and microcracks.

[0026] Furthermore, this invention incorporates the aforementioned borosilicate-aluminum composite modified waste ceramic powder into an inner transition layer that directly contacts the ceramic body, concentrating its strengthening effect on the interface region between the body and the coating where defects are easily formed; the outer strengthening layer further strengthens the ceramic surface. After the inner transition layer, outer strengthening layer, and ceramic green body are co-fired once to form an integral structure, interface porosity and stress concentration can be reduced, and crack propagation from the surface and interface into the body can be inhibited. Thus, while reducing the amount of high-alumina reinforcing raw materials such as calcined bauxite, a high modulus of fracture, breaking strength, and coating tensile bond strength are still maintained, achieving the goals of resource utilization of construction waste, interface strengthening of waste ceramics, and low-cost improvement of ceramic tile strength.

[0027] Furthermore, the preparation of the borosilicate-aluminum composite modified waste ceramic micro powder includes the following steps:

[0028] S1. The cleaned waste ceramic wall and floor tiles are crushed, ground, and passed through a 400-600 mesh sieve to obtain waste ceramic micro powder; 90-110 parts by weight of the waste ceramic micro powder are added to 250-350 parts by weight of water, and stirred and dispersed at 50-70℃ and 400-600 rpm for 20-40 min to obtain waste ceramic micro powder dispersion.

[0029] S2. Dissolve 8-12 parts by weight of aluminum sulfate octadecylhydrate in 80-120 parts by weight of water to obtain an aluminum salt solution; under stirring conditions of 50-70℃ and 400-600 rpm, add the aluminum salt solution to the above-mentioned waste ceramic powder dispersion, adjust the pH of the system to 9.3-9.7 with 0.8-1.2 mol / L sodium hydroxide aqueous solution, and continue stirring for 45-90 min. After the reaction is completed, perform solid-liquid separation, and wash the obtained solid with water 2-4 times to obtain waste ceramic powder modified with aluminum precursor components.

[0030] S3. Add the aluminum-containing precursor modified waste ceramic powder obtained in step S2 to 150-250 parts by weight of water, and stir and disperse at 50-70℃ and 400-600 rpm for 15-30 min; dissolve 0.3-0.8 parts by weight of boric acid in 8-15 parts by weight of water at 50-70℃, mix it evenly with 6-10 parts by weight of silica sol with a solid content of 25-35 wt%, and then add it to the above aluminum-containing precursor modified waste ceramic powder dispersion, and continue stirring at 50-70℃ and 400-600 rpm for 20-40 min; dry the resulting slurry at 100-110℃ to constant weight, pulverize it and pass it through a 300-500 mesh sieve to obtain borosilicate-aluminum composite modified waste ceramic powder.

[0031] The above reaction mechanism: In step S2, aluminum sulfate octadechydrate dissolves in water to form Al 3+Under the action of sodium hydroxide, hydrolysis precipitation occurs, forming an aluminum-containing precursor component mainly composed of Al(OH)3 and aluminum hydroxyl species, which is adsorbed and loaded onto the surface of waste ceramic powder. After solid-liquid separation and water washing, soluble salts in the system are removed. In step S3, the Si-OH on the surface of the silica sol comes into full contact with the Al-OH on the surface of the aluminum-containing precursor component, and dehydration condensation occurs during subsequent drying and co-firing, which is conducive to the formation of Si-O-Al linkage structure. Boric acid mainly exists in the form of B(OH)3, which can form hydrogen bonds with Si-OH and Al-OH, and further participates in the formation of borosilicate aluminum network structure during subsequent co-firing.

[0032] Preferably, the aluminum salt is aluminum sulfate octadechydrate; the pH of the system is adjusted to 9.3-9.7 using sodium hydroxide aqueous solution during the modification process of the aluminum-containing precursor component; and the solid content of the silica sol is 25-35 wt%.

[0033] Preferably, the inner transition layer is formed directly on the surface of the ceramic green body, and the outer reinforcing layer is formed on the outside of the inner transition layer; the dried thickness of the inner transition layer is 20-30 μm, and the dried thickness of the outer reinforcing layer is 50-60 μm.

[0034] Preferably, in step (3), the sintering temperature is 1100-1200℃, and the inner transition layer, outer reinforcing layer and ceramic green body are co-fired together to form an integrated structure during the sintering process.

[0035] A modified coated building ceramic composite material includes a building ceramic matrix and a modified coating formed on the surface of the building ceramic matrix, wherein the building ceramic matrix contains recycled components of construction waste formed from waste ceramics and waste building glass;

[0036] The modified coating includes an inner transition layer directly bonded to the surface of the building ceramic substrate and an outer reinforcing layer located outside the inner transition layer;

[0037] The inner transition layer is formed by sintering an inner transition layer raw material including boron-silicon-aluminum composite modified waste ceramic powder. The boron-silicon-aluminum composite modified waste ceramic powder is obtained by sequentially surface modifying waste ceramic powder with aluminum-containing components and boron-silicon components including silica sol and boric acid.

[0038] The building ceramic matrix, inner transition layer and outer reinforcing layer are co-fired to form an integrated structure.

[0039] Preferably, based on a total of 100 parts by weight of solid raw materials forming the building ceramic matrix, the calcined bauxite comprises 1-5 parts by weight; in the solid raw materials forming the inner transition layer, the borosilicate-alumina composite modified waste ceramic micro powder accounts for 4-12% of the total mass of the solid raw materials, and the inner transition layer is located between the building ceramic matrix and the outer reinforcing layer.

[0040] The beneficial effects of this invention are:

[0041] 1. This invention uses waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass as the main recycled raw materials for building ceramics, which can improve the resource utilization of construction waste in ceramic products and reduce the consumption of natural ceramic mineral raw materials. At the same time, by using modified coatings to undertake part of the strengthening effect, the use of high-alumina reinforcing raw materials such as calcined bauxite in the body can be reduced, which is conducive to reducing raw material costs.

[0042] 2. This invention employs aluminum-containing components to pretreat waste ceramic powder, followed by composite surface modification using silica sol and boric acid, resulting in the distribution of silicon, aluminum, and boron-containing components on the surface of the waste ceramic particles. Compared to unmodified waste ceramic powder or directly adding the modifying components to the coating, this treatment method is more conducive to improving the interfacial bonding between the waste ceramic particles and the sintered aluminosilicate phase, reducing interfacial porosity and micro-defects, and increasing the bonding strength between the inner transition layer and the ceramic matrix.

[0043] 3. The present invention sequentially sets an inner transition layer and an outer reinforcing layer on the surface of a ceramic matrix. The inner transition layer is used to improve the interfacial bonding between the ceramic matrix with high construction waste content and the coating, and the outer reinforcing layer further improves the crack resistance of the ceramic surface. After one co-firing, the ceramic matrix, the inner transition layer and the outer reinforcing layer form an overall synergistic reinforcing structure, thereby improving the fracture modulus and breaking strength of the composite material. Good mechanical properties can still be obtained while reducing the amount of high alumina reinforcing raw materials. Detailed Implementation

[0044] The invention will now be described in further detail with reference to specific embodiments, but it should not be construed as limiting the scope of the invention to the following embodiments.

[0045] The raw materials described in this application are partially described; all other raw materials not described are commercially available.

[0046] Sodium polyacrylate was purchased from Shuangcheng Chemical Products Factory in Renqiu City, model number: 0687.

[0047] Sodium carboxymethyl cellulose was purchased from Guangzhou Donghong Chemical Co., Ltd., model: CMC FH9.

[0048] The silica sol was purchased from Guangzhou Fuer Chemical Technology Co., Ltd., with a solid content of 30%.

[0049] Example 1

[0050] A method for preparing a modified coated building ceramic composite material includes the following steps:

[0051] (1) Pretreatment of construction waste raw materials: waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass are selected as construction waste raw materials; among them, waste building glass is ordinary sodium calcium silicon building glass; metal, wood, plastic, gypsum, cement mortar and other impurities are removed from waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass respectively, and after washing, they are dried at 105℃ to constant weight, and then crushed for later use; among them, a portion of waste ceramic wall and floor tiles and waste building glass are ground separately and passed through a 500-mesh sieve respectively for subsequent preparation of modified coatings;

[0052] (2) Preparation of building ceramic blanks: Weigh 39 parts of waste ceramic wall and floor tiles, 20 parts of waste sintered clay bricks, 12 parts of waste building glass, 16 parts of kaolin, 8 parts of potassium sodium feldspar, 3 parts of calcined bauxite and 2 parts of bentonite by weight; mix the above raw materials and add them to a ball mill with a mass ratio of solid raw materials, grinding balls and water of 1:2:0.8, ball mill for 1.5 h, and pass through a 200-mesh sieve; dry the obtained slurry at 90℃, pulverize it and add 5.5% water relative to the dry powder mass for granulation, pass through a 20-mesh sieve and seal and age for 12 h to obtain building ceramic blanks;

[0053] (3) Preparation of ceramic green body: The building ceramic blank obtained in step (2) is pressed into a ceramic green body of 300 mm × 300 mm × 8 mm under a molding pressure of 32 MPa. The ceramic green body is dried at 110℃ for 2 h to obtain a dried ceramic green body.

[0054] (4) The inner transition layer slurry is uniformly coated on the two opposing main surfaces of the dried ceramic green body obtained in step (3). After coating the inner transition layer slurry, it is pre-dried at 80°C for 10 min to make the inner transition layer surface dry. The thickness of the inner transition layer after drying is controlled to be 25 μm. Then, the outer strengthening layer slurry is coated on the surface of the inner transition layer. After coating, it is dried at 100°C for 30 min to control the thickness of the outer strengthening layer after drying to be 55 μm. A ceramic green body with a double-layer modified coating is obtained.

[0055] (5) Place the ceramic green body obtained in step (4) in a sintering furnace, raise the temperature to 600°C at 5°C / min, raise the temperature to 1140°C at 3°C / min, hold at 1140°C for 30 min, and then cool to room temperature to obtain the modified coated building ceramic composite material.

[0056] The preparation of the inner transition layer slurry in step (4) is as follows: 17 parts by weight of waste ceramic micro powder, 8 parts by weight of borosilicate aluminum composite modified waste ceramic micro powder, 30 parts by weight of waste glass powder, 28 parts by weight of wollastonite, 15 parts by weight of calcined kaolin, and 2 parts by weight of zinc oxide are mixed, and 48 parts by weight of water, 0.30 parts by weight of sodium polyacrylate and 0.35 parts by weight of sodium carboxymethyl cellulose are added and mixed. The mixture is ball-milled for 2 hours and passed through a 500-mesh sieve to obtain the inner transition layer slurry.

[0057] The preparation method of the borosilicate-aluminum composite modified waste ceramic micro powder is as follows:

[0058] S1. The cleaned waste ceramic wall and floor tiles are crushed, ground, and passed through a 500-mesh sieve to obtain waste ceramic micro powder; 100 parts by weight of the waste ceramic micro powder are added to 300 parts by weight of water and stirred and dispersed at 60℃ and 500rpm for 30 minutes to obtain waste ceramic micro powder dispersion.

[0059] S2. Dissolve 10.0 parts by weight of aluminum sulfate octadechydrate in 100 parts by weight of water to obtain an aluminum salt solution; under stirring conditions of 60℃ and 500 rpm, add the aluminum salt solution to the above-mentioned waste ceramic powder dispersion, and adjust the pH to 9.3-9.7 with 1.0 mol / L sodium hydroxide aqueous solution; continue stirring for 60 min to load the aluminum-containing precursor component onto the surface of the waste ceramic powder; after the reaction is completed, perform solid-liquid separation, and wash the obtained solid three times with water to obtain waste ceramic powder modified with aluminum-containing precursor component;

[0060] S3. Add the aluminum-containing precursor modified waste ceramic powder obtained in step S2 to 200 parts by weight of water, and stir and disperse at 60°C and 500 rpm for 20 min to obtain a dispersion of aluminum-containing precursor modified waste ceramic powder; dissolve 0.5 parts by weight of boric acid in 10 parts by weight of water at 60°C, and stir at 500 rpm until the boric acid is completely dissolved to obtain a boric acid aqueous solution; mix the obtained boric acid aqueous solution with 8 parts by weight of silica sol with a solid content of 30 wt%, and then add it to the above aluminum-containing precursor modified waste ceramic powder dispersion, and continue stirring at 60°C and 500 rpm for 30 min; dry the obtained slurry at 105°C to constant weight, pulverize and pass through a 400-mesh sieve to obtain borosilicate-aluminum composite modified waste ceramic powder.

[0061] The preparation of the external reinforcing layer slurry in step (4) is as follows: 58 parts by weight of wollastonite, 20 parts by weight of quartz powder, 9 parts by weight of calcined kaolin, 10 parts by weight of waste glass powder, and 3 parts by weight of zinc oxide are mixed, and 48 parts by weight of water, 0.30 parts by weight of sodium polyacrylate and 0.35 parts by weight of sodium carboxymethyl cellulose are added and mixed. The mixture is ball-milled for 2 hours and passed through a 500-mesh sieve to obtain the external reinforcing layer slurry.

[0062] Example 2

[0063] The process is basically the same as in Example 1, except that the solid raw materials of the inner transition layer slurry include, by weight, 21 parts of waste ceramic powder, 4 parts of borosilicate-alumina composite modified waste ceramic powder, 30 parts of waste glass powder, 28 parts of wollastonite, 15 parts of calcined kaolin, and 2 parts of zinc oxide; the composition and preparation method of the remaining raw materials are the same as in Example 1.

[0064] Example 3

[0065] The process is basically the same as in Example 1, except that the solid raw materials of the inner transition layer slurry include, by weight, 13 parts of waste ceramic powder, 12 parts of borosilicate-alumina composite modified waste ceramic powder, 30 parts of waste glass powder, 28 parts of wollastonite, 15 parts of calcined kaolin, and 2 parts of zinc oxide; the composition and preparation method of the remaining raw materials are the same as in Example 1.

[0066] Example 4

[0067] The process is basically the same as in Example 1, except that the building ceramic blanks in step (2) include, by weight, 41 parts of waste ceramic wall and floor tiles, 20 parts of waste sintered clay bricks, 12 parts of waste building glass, 16 parts of kaolin, 8 parts of potassium sodium feldspar, 1 part of calcined bauxite and 2 parts of bentonite; the composition and preparation method of the remaining raw materials are the same as in Example 1.

[0068] Example 5

[0069] The process is basically the same as in Example 1, except that the building ceramic blanks in step (2) include, by weight, 37 parts of waste ceramic wall and floor tiles, 20 parts of waste sintered clay bricks, 12 parts of waste building glass, 16 parts of kaolin, 8 parts of potassium sodium feldspar, 5 parts of calcined bauxite and 2 parts of bentonite; the composition and preparation method of the remaining raw materials are the same as in Example 1.

[0070] Comparative Example 1

[0071] The process is basically the same as in Example 1, except that: no boron-silicon-aluminum composite modified waste ceramic powder is added to the inner transition layer slurry, and an equal weight of unmodified waste ceramic powder is used instead; the solid raw materials of the inner transition layer slurry include, by weight, 25 parts waste ceramic powder, 30 parts waste glass powder, 28 parts wollastonite, 15 parts calcined kaolin and 2 parts zinc oxide; all other conditions are the same as in Example 1.

[0072] Comparative Example 2

[0073] The process is basically the same as in Example 1, except that: no boron component is introduced; in the preparation process of the borosilicate-aluminum composite modified waste ceramic powder, 0.5 parts by weight of boric acid is not added in step S3; the amount of other raw materials and preparation conditions are the same as in Example 1; silicon-aluminum composite modified waste ceramic powder is obtained; and the borosilicate-aluminum composite modified waste ceramic powder in Example 1 is replaced with an equal amount of the obtained silicon-aluminum composite modified waste ceramic powder; all other conditions are the same as in Example 1.

[0074] Comparative Example 3

[0075] The process is basically the same as in Example 1, except that: no silica sol is introduced; in the preparation of the boron-silicon-aluminum composite modified waste ceramic powder, step S3 does not involve adding 8 parts by weight of silica sol with a solid content of 30 wt%, but instead dissolves 0.5 parts by weight of boric acid in 10 parts by weight of water at 60°C and adds it to the dispersion of waste ceramic powder modified with aluminum precursor components. The remaining preparation conditions are the same as in Example 1, and boron-aluminum composite modified waste ceramic powder is obtained. An equal amount of the obtained boron-aluminum composite modified waste ceramic powder is used to replace the boron-silicon-aluminum composite modified waste ceramic powder in Example 1; the remaining conditions are the same as in Example 1.

[0076] Comparative Example 4

[0077] The process is basically the same as in Example 1, except that: the aluminum-containing component is not pre-modified, and step S2 is omitted when preparing the modified waste ceramic powder; after the waste ceramic powder dispersion is obtained in step S1, a mixture consisting of 0.5 parts by weight of boric acid and 8 parts by weight of silica sol with a solid content of 30 wt% is directly added, and the mixture is stirred at 60°C and 500 rpm for 30 min, then dried at 105°C, pulverized, and passed through a 400-mesh sieve to obtain borosilicate composite modified waste ceramic powder; an equal amount of the obtained borosilicate composite modified waste ceramic powder is used to replace the borosilicate aluminum composite modified waste ceramic powder in Example 1; all other conditions are the same as in Example 1.

[0078] Comparative Example 5

[0079] The process is basically the same as in Example 1, except that the building ceramic blanks in step (2) include, by weight, 36 parts of waste ceramic wall and floor tiles, 20 parts of waste sintered clay bricks, 12 parts of waste building glass, 16 parts of kaolin, 8 parts of potassium sodium feldspar, 6 parts of calcined bauxite and 2 parts of bentonite; the other conditions are the same as in Comparative Example 1.

[0080] Comparative Example 6

[0081] The process is basically the same as in Example 1, except that in step (4), the inner transition layer slurry described in Example 1 is coated only on the two opposite main surfaces of the ceramic green body, and the outer reinforcing layer is no longer coated; the thickness of the inner transition layer after drying is controlled to be 25 μm, and then dried at 100°C for 30 min; the composition of other raw materials and preparation conditions are the same as in Example 1.

[0082] Test Example 1

[0083] The modified coated building ceramic composite materials prepared in Examples 1-5 and Comparative Examples 1-6 were used as test samples. Tests were conducted according to GB / T 3810.4-2016 "Ceramic Tiles - Test Methods Part 4: Determination of Modulus of Fracture and Breaking Strength", with 10 samples taken from each group. During the test, the breaking load F at fracture of each specimen was recorded, and the breaking strength S was calculated based on the specimen width and the distance between the support rods. After the specimen fractured, the actual minimum thickness h of each specimen was measured at the fracture edge, and the modulus of fracture R was calculated using the measured thickness of each specimen. After calculation for each specimen, the arithmetic mean of the test results of the 10 specimens was taken as the breaking strength and modulus of fracture for that group of samples.

[0084] Test Example 2

[0085] Coating tensile bond strength test: Take the composite materials prepared in Examples 1-5 and Comparative Examples 1-6 respectively, test the tensile bond strength of the coating system formed by the modified coating and the ceramic matrix, and record the main failure location of the sample; when internal failure of the adhesive occurs, the data is invalid and the test is repeated.

[0086] The test was conducted with reference to the loading and bond strength evaluation principles of GB / T 39685-2020 "Test Method for Bond Strength of Ceramic Coatings", with the following adjustments made. The specific test method is as follows:

[0087] Each group of samples was cut into 50 mm × 50 mm specimens. After cleaning the test surface, for Examples 1-5 and Comparative Examples 1-5, the drawing head was bonded to the surface of the outer reinforcing layer, and an annular groove was cut along the outer edge of the drawing head so that the annular groove penetrates the outer reinforcing layer and the inner transition layer to the surface of the ceramic substrate. For Comparative Example 6, the drawing head was bonded to the surface of the inner transition layer, and the annular groove penetrates the inner transition layer to the surface of the ceramic substrate.

[0088] A pull-out adhesion tester was used to uniformly apply a load perpendicular to the sample surface at a rate of 0.5 MPa / s until the sample failed. The maximum pull-out load F was recorded. The tensile bond strength of the coating was calculated using the following formula:

[0089] Coating tensile bond strength σ=F / A

[0090] In the formula, σ represents the tensile bond strength of the coating, in MPa; F represents the maximum pull-out load, in N; and A represents the effective bonding area of ​​the pull-out head, in mm². Five valid samples are tested in each group, and the average value is taken as the tensile bond strength of the coating.

[0091] Test Example 3

[0092] Coating-substrate interface pore area ratio test: The composite materials prepared in Examples 1-5 and Comparative Examples 1-6 were cut along a direction perpendicular to the surface of the modified coating, and the cross section containing the ceramic matrix and the inner transition layer was taken as the test surface; for the sample with an outer reinforcing layer, the cross section also contains the outer reinforcing layer.

[0093] After resin inlay, the cross-section was ground and polished in sequence, and the bonding area between the inner transition layer and the ceramic substrate was observed using a scanning electron microscope at 500x magnification.

[0094] Centered on the interface between the inner transition layer and the ceramic matrix, a region of 50 μm is taken on both the inner transition layer side and the ceramic matrix side, that is, a region with a total width of 100 μm and a length of 1.0 mm, as the statistical region of the interface porosity.

[0095] Image analysis software was used to convert the cross-sectional image into a grayscale image. A uniform threshold was used to distinguish between the porous region and the ceramic solid region. The interface porosity was calculated using the following formula:

[0096] Interface porosity = Porosity area within the statistical region of the interface / Total area of ​​the statistical region of the interface × 100%.

[0097] Five different interface locations were randomly selected for testing on each sample, and the average value of the test results at the five locations was taken as the interface porosity of the sample.

[0098] All samples were analyzed using the same sample preparation method, magnification, image brightness, and threshold conditions.

[0099] Table 1 Test results of modified coated architectural ceramic composite materials

[0100] Example 1 128.4 5478 6.82 1.5 Example 2 106.7 4553 5.21 3.0 Example 3 112.9 4817 5.69 2.5 Example 4 102.6 4326 5.26 2.9 Example 5 120.1 5024 6.18 1.9 Comparative Example 1 75.8 3234 2.95 7.2 Comparative Example 2 94.6 4036 4.31 4.3 Comparative Example 3 88.9 3793 3.78 5.1 Comparative Example 4 91.7 3913 3.96 4.8 Comparative Example 5 104.2 4446 3.21 6.6 Comparative Example 6 101.8 4161 6.12 1.8

[0101] The results from Examples 1-3 and Comparative Example 1 show that introducing borosilicate-alumina composite modified waste ceramic powder into the inner transition layer can significantly improve the fracture modulus, breaking strength, and tensile bond strength of the building ceramic composite material, while reducing the interfacial porosity. This is because the waste ceramics have already undergone high-temperature firing, resulting in low surface reactivity. The bonding between the untreated waste ceramic powder and the glassy phase and aluminosilicate sintered phase formed in the inner transition layer during re-sintering is relatively weak. After sequential composite modification with aluminum-containing components, silica sol, and boric acid, the contact and wetting state between the waste ceramic powder surface and the surrounding sintered components is improved, and interfacial bonding during co-firing is promoted, thereby reducing interfacial porosity and micro-defects and improving interfacial load-bearing capacity. In Example 2, the amount of borosilicate aluminum composite modified waste ceramic powder was relatively low, and its effect on improving the interface was relatively limited. In Example 3, after the amount of modified waste ceramic powder was further increased, although the performance was still significantly better than that of Comparative Example 1, the overall performance did not continue to improve. This indicates that the amount of modified waste ceramic powder added is not necessarily better the higher it is. Excessive addition may change the sintering composition of the inner transition layer and the liquid phase formation state.

[0102] As shown in Example 1 and Comparative Examples 2-4, when boric acid, silica sol, or aluminum-containing precursor components are lacking in the boron-silicon-aluminum composite modification system, the fracture modulus, breaking strength, and tensile bond strength of the resulting composite material all decrease to varying degrees, while the interfacial porosity increases. This indicates that boron, silicon, and aluminum all have corresponding effects on the composite surface modification of waste ceramic powder. Pretreatment with aluminum-containing precursor components is beneficial to improving the subsequent modification state of the waste ceramic powder surface. Silica sol can provide siliceous components and participate in the formation of the sintering interface, while boric acid is beneficial to improving the formation of the liquid phase and interfacial wetting during the subsequent sintering process. When the three are used in combination according to the method described in this invention, a comprehensive strengthening effect superior to that without any one component can be obtained, indicating a synergistic effect between boron, silicon, and aluminum components.

[0103] The results of Examples 4, 1, and 5 show that, under the condition of using borosilicate-alumina composite modified waste ceramic powder, an inner transition layer, and an outer reinforcing layer, the amount of calcined bauxite affects the overall mechanical properties of the material. When the amount of calcined bauxite is low, its reinforcing effect on the ceramic body is insufficient; appropriately increasing its amount can improve the material's load-bearing capacity, but further increasing the amount of calcined bauxite does not lead to a sustained improvement in material properties. This indicates that in the interface modification and double-layer coating reinforcement system of this invention, there is a suitable amount of calcined bauxite to add, and it is not necessary to simply increase the amount of high-alumina reinforcing raw materials to obtain higher strength.

[0104] Comparative Examples 1 and 5 show that, without using borosilicate-alumina composite modified waste ceramic powder, increasing the amount of calcined bauxite in the green body can improve the rupture modulus and breaking strength of the material to a certain extent. However, the tensile bonding strength of the coating is still low, and the interfacial porosity is still high. This indicates that simply increasing the amount of calcined bauxite mainly strengthens the green body itself and cannot effectively solve the problem of insufficient bonding between waste ceramic particles and the coating-matrix interface. Further, in conjunction with Example 1, it can be seen that this invention achieves synergistic strengthening of the interface and surface through borosilicate-alumina composite modified waste ceramic powder and a double-layer modified coating, obtaining better overall mechanical properties with a lower amount of calcined bauxite.

[0105] As can be seen from Example 1 and Comparative Example 6, after retaining the borosilicate aluminum composite modified waste ceramic powder and the inner transition layer while eliminating the outer reinforcing layer, the changes in the coating tensile bond strength and interfacial porosity of the material are relatively small, while the fracture modulus and breaking strength decrease significantly. This indicates that the inner transition layer is mainly used to improve the interfacial bond between the ceramic matrix and the coating and reduce interfacial defects, while the outer reinforcing layer mainly further improves the load-bearing and bending strengthening capacity of the ceramic surface.

Claims

1. A method for preparing a modified coated architectural ceramic composite material, characterized in that, Includes the following steps: (1) Mix construction waste raw materials, including waste ceramics and waste building glass, with ceramic matrix, and obtain building ceramic blanks by ball milling and granulation. Then, press the building ceramic blanks into shapes to obtain ceramic green bodies. (2) An inner transition layer and an outer reinforcing layer are sequentially formed on the surface of the ceramic green body; wherein, the raw materials of the inner transition layer include waste ceramic powder, borosilicate aluminum composite modified waste ceramic powder, waste glass powder, wollastonite and aluminosilicate raw materials, and the raw materials of the outer reinforcing layer include wollastonite, quartz powder and aluminosilicate raw materials. The boron-silicon-aluminum composite modified waste ceramic powder is obtained by sequentially modifying waste ceramic powder with aluminum-containing components and boron-silicon components including silica sol and boric acid. (3) The ceramic green body with the inner transition layer and the outer reinforcing layer is sintered to make the ceramic green body, the inner transition layer and the outer reinforcing layer co-fired and combined to obtain the modified coating building ceramic composite material.

2. The preparation method according to claim 1, characterized in that, In step (1), the construction waste raw materials include waste ceramic wall and floor tiles, waste sintered clay bricks and waste building glass, and the ceramic base material includes kaolin, potassium sodium feldspar, calcined bauxite and bentonite; Based on a total of 100 parts by weight of solid raw materials for building ceramic blanks, the calcined bauxite comprises 1-5 parts by weight.

3. The preparation method according to claim 1 or 2, characterized in that, In the inner transition layer, boron-silicon-aluminum composite modified waste ceramic powder accounts for 4-12% of the total mass of the solid raw materials in the inner transition layer, and the total amount of waste ceramic powder and boron-silicon-aluminum composite modified waste ceramic powder accounts for 20-30% of the total mass of the solid raw materials in the inner transition layer.

4. The preparation method according to claim 1, characterized in that, The solid raw material of the inner transition layer also includes zinc oxide, and the aluminosilicate raw material includes calcined kaolin; the solid raw material of the outer reinforcing layer also includes waste glass powder and zinc oxide.

5. The preparation method according to claim 1, characterized in that, The preparation method of the borosilicate-aluminum composite modified waste ceramic micro powder includes: Waste ceramic powder was dispersed in water, aluminum salt solution was added and the system was adjusted to alkalinity so that the aluminum-containing precursor component was loaded on the surface of the waste ceramic powder. Subsequently, a borosilicate-modified component, including silica sol and boric acid, was added for composite surface modification. After drying and pulverizing, the borosilicate-aluminum composite modified waste ceramic powder was obtained.

6. The preparation method according to claim 5, characterized in that, The aluminum salt is aluminum sulfate octadechydrate; the pH of the system is adjusted to 9.3-9.7 using sodium hydroxide aqueous solution during the modification process of the aluminum-containing precursor component; the solid content of the silica sol is 25-35 wt%.

7. The preparation method according to any one of claims 1-6, characterized in that, The inner transition layer is formed directly on the surface of the ceramic green body, and the outer reinforcing layer is formed on the outside of the inner transition layer; the dried thickness of the inner transition layer is 20-30 μm, and the dried thickness of the outer reinforcing layer is 50-60 μm.

8. The preparation method according to any one of claims 7, characterized in that, In step (3), the sintering temperature is 1100-1200℃, and the inner transition layer, outer reinforcing layer and ceramic green body are co-fired together to form an integrated structure during the sintering process.

9. A modified coated building ceramic composite material, characterized in that, It includes a building ceramic matrix and a modified coating formed on the surface of the building ceramic matrix, the building ceramic matrix containing recycled components of construction waste formed from waste ceramics and waste building glass; The modified coating includes an inner transition layer directly bonded to the surface of the building ceramic substrate and an outer reinforcing layer located outside the inner transition layer; The inner transition layer is formed by sintering an inner transition layer raw material including boron-silicon-aluminum composite modified waste ceramic powder. The boron-silicon-aluminum composite modified waste ceramic powder is obtained by sequentially surface modifying waste ceramic powder with aluminum-containing components and boron-silicon components including silica sol and boric acid. The building ceramic matrix, inner transition layer and outer reinforcing layer are co-fired to form an integrated structure.

10. The modified coated building ceramic composite material according to claim 9, characterized in that, Based on a total of 100 parts by weight of solid raw materials forming the building ceramic matrix, the calcined bauxite comprises 1-5 parts by weight; in the solid raw materials forming the inner transition layer, the borosilicate-alumina composite modified waste ceramic micro powder accounts for 4-12% of the total mass of the solid raw materials, and the inner transition layer is located between the building ceramic matrix and the outer reinforcing layer.

Citation Information

Patent Citations

  • Prestressed ceramic and preparation method thereof

    CN113264783A

  • Method for recycling waste porcelain and ceramic tile

    CN115650698A

  • Waste ceramic powder and application thereof in ceramic tile

    CN118125800A